Cost-effectiveness analysis of community-led HIV self-testing among key populations in Côte d'Ivoire, Mali, and Senegal - Lu,IJ; Silhol,R; d'Elbée,M; Boily,M-C; Soni,N; Ky-Zerbo,O; Vautier,A; Simo,Fosto A; Badiane,K; Traoré,M; Terris-Prestholt,F; Larmarange,J; et al. (Journal of the International AIDS Society, 2024)
INTRODUCTION: HIV self-testing (HIVST) is a promising strategy to improve diagnosis coverage among key populations (KP). The ATLAS (Auto Test VIH, Libre d'Accéder à la connaissance de son Statut) programme implemented HIVST in three West African countries, distributing over 380,000 kits up between 2019 and 2021, focussing on community-led distribution by KP to their peers and subsequent secondary distribution to their partners and clients. We aim to evaluate the cost-effectiveness of community-led HIVST in Côte d'Ivoire, Mali and Senegal. METHODS: An HIV transmission dynamics model was adapted and calibrated to country-specific epidemiological data and used to predict the impact of HIVST. We considered the distribution of HIVST among two KP-female sex workers (FSW), and men who have sex with men (MSM)-and their sexual partners and clients. We compared the cost-effectiveness of two scenarios against a counterfactual without HIVST over a 20-year horizon (2019-2039). The ATLAS-only scenario mimicked the 2-year implemented ATLAS programme, whereas the ATLAS-scale-up scenario achieved 95% coverage of HIVST distribution among FSW and MSM by 2025 onwards. The primary outcome is the number of disability-adjusted life-years (DALY) averted. Scenarios were compared using incremental cost-effectiveness ratios (ICERs). Costing was performed using a healthcare provider's perspective. Costs were discounted at 4%, converted to $USD 2022 and estimated using a cost-function to accommodate economies of scale. RESULTS: The ATLAS-only scenario was highly cost-effective over 20 years, even at low willingness-to-pay thresholds. The median ICERs were $126 ($88-$210) per DALY averted in Côte d'Ivoire, $92 ($88-$210) in Mali and 27$ ($88-$210) in Senegal. Scaling-up the ATLAS programme would also be cost-effective, and substantial epidemiological impacts would be achieved. The ICERs for the scale-up scenario were $199 ($122-$338) per DALY averted in Côte d'Ivo